2022
DOI: 10.3389/fphys.2022.943612
|View full text |Cite
|
Sign up to set email alerts
|

A review of heat stress in chickens. Part II: Insights into protein and energy utilization and feeding

Abstract: With the growing global demand for animal protein and rising temperatures caused by climate change, heat stress (HS) is one of the main emerging environmental challenges for the poultry industry. Commercially-reared birds are particularly sensitive to hot temperatures, so adopting production systems that mitigate the adverse effects of HS on bird performance is essential and requires a holistic approach. Feeding and nutrition can play important roles in limiting the heat load on birds; therefore, this review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 200 publications
0
12
1
2
Order By: Relevance
“…This therefore confirms that feeding diets high in arginine improves the performance of broilers under TN conditions. On the other hand, cyclic exposure to high environmental temperatures considerably impaired growth performance, reducing FI and BW gain, and increased body temperature and mortality, thereby causing some of the adverse effects typically observed in heat-stressed chickens (Brugaletta et al, 2022;Teyssier et al, 2022). Arginine supplementation, however, did not alleviate the deterioration in performance or prevent environmentally induced hyperthermia, as the birds responded similarly to the thermal stress irrespective of the diet they were fed on.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This therefore confirms that feeding diets high in arginine improves the performance of broilers under TN conditions. On the other hand, cyclic exposure to high environmental temperatures considerably impaired growth performance, reducing FI and BW gain, and increased body temperature and mortality, thereby causing some of the adverse effects typically observed in heat-stressed chickens (Brugaletta et al, 2022;Teyssier et al, 2022). Arginine supplementation, however, did not alleviate the deterioration in performance or prevent environmentally induced hyperthermia, as the birds responded similarly to the thermal stress irrespective of the diet they were fed on.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, precise and consistent arginine requirements for broilers under HS are not readily available in the literature. Alterations in feed intake, physiology, metabolism, and gut health and function induced by HS contribute to complicating the calculation of arginine or other nutrient needs for heatstressed broilers (Teyssier et al, 2022). For example, considering the "ideal protein" concept widely adopted in poultry nutrition (Wiseman and Garnsworthy, 1999), Balnave and Brake (2002) attributed the increased arginine to lysine ratios in broilers undergoing HS to a likely reduction in intestinal absorption of arginine.…”
Section: Introductionmentioning
confidence: 99%
“…La adición de grasas en la dieta es una alternativa para mejorar los rendimientos ya que los lípidos tienen un efecto termogénico menor en comparación con las proteínas y los carbohidratos. La suplementación de algunos aminoácidos esenciales puede ayudar también en el incremento de los rendimientos (Teyssier et al, 2022).…”
Section: El Medio Ambiente En La Digestión De Las Proteínasunclassified
“…However, pair-feeding models—adopted to minimize the confounding effects of dissimilar feed consumption between birds under thermoneutral conditions and their heat-stressed counterparts—revealed that up to 40% of body weight gain loss of broilers subjected to HS are unrelated to anorexia ( Dale and Fuller, 1980 ; Geraert et al, 1996a ; Ain Baziz et al, 1996 ; Lu et al, 2007 ; Zuo et al, 2015 ; Lu et al, 2018 ; Teyssier et al, 2022b ). Readers are referred to Part II of this review series for more information on the effects of HS on feed intake ( Teyssier et al, 2022a ). Table 1 provides an overview of heat stress effects on chicken behavior.…”
Section: Heat Stress Effects On Physiology Of Chickensmentioning
confidence: 99%
“…Therefore, this review series composed of Part I and Part II, was conceived to summarize relevant knowledge about these topics and examine some feeding and nutritional interventions that have been proposed to mitigate HS in broiler chickens. The present Part I discusses the effects of HS on physiology and gut health of chickens, while Part II ( Teyssier et al, 2022a ) provides an overview of potential solutions employed in broiler chicken nutrition to minimize the detrimental effects of HS.…”
Section: Introductionmentioning
confidence: 99%